The personality traits of a sports coach and their relationship to learning motivation among beginners - Aroussi, abdrazek (sports creativity, 2025)
Osama Kamel Rateb indicates that the aim of studying the behavior and characteristics of the individual athlete is to try to discover the psychological reasons and factors that influence the athlete's behavior. The sports coach is considered an educational figure who directly influences the players' personalities and achievements. This depends primarily on the characteristics, traits, abilities, knowledge, and skills of the sports coach. The kinesthetic learning process for beginners in football is considered the golden age of the learning process, and this leads us to search for the personality traits of the sports coach and their relationship to learning motivation in football schools.